Knowledge, attitude , and perception of Kapampangan consumers towards selected commercially available traditional Kapampangan Foods (TKFs) - Baluyut, Carl Katley L.; Pagulayan, Jin Mark DG (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
Despite their significance to the community’s culture, traditional Kapampangan foods (TKFs) experience market challenges due to shifting preferences and perceptions of the consumers and unstructured marketing strategies used by micro, small, and medium enterprises (MSMEs), failing to satisfy consumer requirements. To aid MSMEs understand the behavior of the consumers of their products, the study investigated the consumer knowledge, attitude, and perception of Kapampangans towards selected TKFs (i.e., Sanikulas, burung asan, and pindang babi and damulag) through a survey. Using Exploratory Factor Analysis (EFA), factors were generated for each assessed parameter, which suggests that Kapampangan consumers generally exhibit a fair-to-high level of knowledge and favorable attitude toward traditional foods. Results also indicate that they perceive an extremely high level of importance to the safety and taste/flavor of the TKFs, which also corresponds to their high regard for their intrinsic quality attributes. Hierarchical Cluster Analysis and K-Means Cluster Analysis applied to the formerly generated factors revealed four clusters of consumers: (1) quality-seeking, (2) brand-addicted, (3) casual, and (4) convenience-oriented consumers that were established
and differentiated using their heterogeneous level of knowledge, attitude, and quality perception of TKFs. These consumer segments, characterized by their behavior, could be leveraged by MSMEs offering the selected TKFs in applying various types of innovations to their products.
Thesis (Bachelor of science in Food Technology) -- University of the Philippines Diliman
Bibliography : pages 66-78.
Keywords: Cooking, Filipino -- Kapampangan; Kampampangan food; Consumer behavior -- Food -- Philippines -- Pampanga